Corporate Characteristics Determining Sustainability Reporting - Sahar Yousefizadeh; Hossein Fakhari (پژوهش‌های تجربی حسابداری)
Considering the importance of sustainability reporting among stakeholders, this research aims to explain a model for internal organizational factors affecting sustainability reporting disclosure. Such a model can help account thinkers and company managers understand the factors influencing sustainability report quality. we obtain the organizational factors influencing sustainability reporting with first-order factor analysis, and then, along with other variables of the research, we obtain the effect of the obtained organizational factors on the disclosure score of sustainable reporting. Then we obtain the consequences of sustainability reporting with seemingly unrelated regression methods. The research sample also includes information related to 194 Tehran Stock Exchange companies, for the fiscal years 1390 to 1400, compiled from financial statements, management reports, and audit committee information. The findings based on the measurement model and first-order confirmatory factor analysis show that twenty factors can be effective in reporting sustainability. We have obtained the effect of these factors on the disclosure score of the sustainability report and then we have examined the consequences of sustainability reporting. The results show that the factors affecting the sustainability report are classified in the form of eight dimensions company size, board of directors, ownership structure, regulatory structure and corporate governance structure, strategicness of the industry, profitability, and financial leverage. Also, there is a reciprocal relationship between sustainability report disclosure and return on equity